Genetic variability and disease severity in a cohort of Angolan sickle cell disease patients - Brito, Miguel (2022)
Purpose: Sickle Cell Anaemia (SCA) is an inherited autosomal and lethal blood disorder caused by a mutation in the HBB gene that promotes haemoglobin (Hb) polymerization and consequent sickling of red blood cells (RBCs) in hypoxia. Regardless of being a monogenic disease, SCA has a remarkably high clinical heterogeneity in its phenotypic expression. Several factors have been shown to modulate the clinical manifestations of SCA, namely genetic markers such as α-thalassaemia and β-globin cluster haplotypes, that can modulate biological parameters like the degree of haemolytic anaemia or the levels of foetal haemoglobin (HbF).